Application of SQ3R Learning Method in Improving Mathematics Learning Outcomes in Quadrangular Basic Competencies Class VIIB students of MTs Almawaddah Warahmaah Kolaka - Gemi Susanti (JME (Journal of Mathematics Education), 2020)
The purpose of this study was to find out that the application of the SQ3R learning method can improve mathematics learning outcomes in the quadrilateral basic competencies of class VIIB students at MTs Almawaddah Warahmah Kolaka. This research includes classroom action research (CAR) or classroom action research. The procedure of this research is planning, action implementation, observation and evaluation, and reflection. The sources of data in this study were mathematics teachers and students. The type of data obtained is quantitative data, namely student learning outcomes and qualitative data, namely observation sheets. This research was conducted in class VIIB of MTs Almawaddah Warahmah Kolaka in the 2010/2011 academic year even semester. with the number of students 12. From the results of data analysis concluded: (1). The activity of the teacher (researcher) experienced a significant increase from cycle I to cycle II where the learning process was in accordance with what was contained in the lesson plans and observation sheets, (2). Student activities showed a significant increase where they became more active during the learning process and dared to show off their work/reports in front of the class, (3) The application of the SQ3R learning method could improve student learning outcomes for class VIIB MTs Almawaddah Warahmah Kolaka, where the average results learning during the first cycle of 43.33 or completeness of 41.66% increased in the second cycle of 67.5 or completeness of 83.33%.